2020
DOI: 10.3389/fpls.2020.00117
|View full text |Cite
|
Sign up to set email alerts
|

Origin, Diversity, and Evolution of Telomere Sequences in Plants

Abstract: Telomeres are basic structures of eukaryote genomes. They distinguish natural chromosome ends from double-stranded breaks in DNA and protect chromosome ends from degradation or end-to-end fusion with other chromosomes. Telomere sequences are usually tandemly arranged minisatellites, typically following the formula (T x A y G z) n. Although they are well conserved across large groups of organisms, recent findings in plants imply that their diversity has been underestimated. Changes in telomeres are of enormous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 88 publications
1
60
0
Order By: Relevance
“…[22,38,46]. Unlike insects, even the unusual plant telomeric sequences characterized so far are synthesized by telomerases using TRs with corresponding template regions [19,43,44,47].…”
Section: The Origin Of Telomerasementioning
confidence: 99%
“…[22,38,46]. Unlike insects, even the unusual plant telomeric sequences characterized so far are synthesized by telomerases using TRs with corresponding template regions [19,43,44,47].…”
Section: The Origin Of Telomerasementioning
confidence: 99%
“…In most flowering plants, telomeric sequences are very similar (5′-TTTAGGG-3′) ( Richards and Ausubel 1988 ; Richards et al. 1992 ; Shippen and McKnight 1998 ; Peška and Garcia 2020 ) or even identical to the vertebrate motif (e.g., several species belonging to the order Asparagales or Zostera marina ) ( Sýkorová, Lim, Kunická, et al. 2003 ; Sýkorová et al.…”
Section: Introductionmentioning
confidence: 99%
“…When telomerase is not active, telomeres become shortened, and their function in the protection of chromosomes is disrupted. The extreme evolutionary success of telomerase-based mechanisms of telomere maintenance is illustrated by current findings in plants (reviewed in [ 14 ]). Even among apparent exceptions in telomere sequences, in plant genera Allium (Asparagales) and Cestrum (Solanales) [ 15 , 16 , 17 , 18 ], recent research has revealed that novel, unusual telomere DNA sequences are synthesized by telomerase [ 16 , 18 , 19 ] and not by alternative mechanisms as had been suggested previously (reviewed in [ 20 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Even among apparent exceptions in telomere sequences, in plant genera Allium (Asparagales) and Cestrum (Solanales) [ 15 , 16 , 17 , 18 ], recent research has revealed that novel, unusual telomere DNA sequences are synthesized by telomerase [ 16 , 18 , 19 ] and not by alternative mechanisms as had been suggested previously (reviewed in [ 20 ]). Moreover, we recently demonstrated that changes in the template region of the telomerase RNA subunit directed the observed evolutionary transitions in telomere DNA sequences [ 14 , 21 , 22 ]. In contrast to the RNA subunit, the protein subunit TERT is evolutionary well conserved and possesses a central reverse transcriptase domain essential for its catalytic function [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%